0035 Long-sleepers and Insomnia with Short Objective Sleep Duration are Independently Associated with Short Telomere Length in the EPISONO Cohort. (27th April 2018) - Tempaku, P F; Hirotsu, C; Mazzotti, D R; Xavier, G; Maurya, P K; Rizzo, L B; Brietzke, E; Belangero, S I; Poyares, D; Bittencourt, L; Tufik, S
Abstract: Introduction: Telomeres are specialized sequences at the end of chromosomes that shorten with aging, and whose length is negatively modulated by genotoxic stressors. Considering the importance of sleep in the homeostasis regulation, we aimed to determine the association between mean leukocyte telomere length (LTL) and sleep parameters as well sleep disorders in an adult general population sample. Methods: As part of the EPISONO cohort (São Paulo, Brazil), 926 individuals answered questionnaires, underwent type 1 polysomnography (PSG) and clinical assessment, and had peripheral blood collected for DNA extraction. Obstructive sleep apnea (OSA) was defined according to apnea-hypopnea index (mild 5≤AHI<15; moderate-severe AHI≥15/h) and insomnia was diagnosed according to the 4 th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV). For the objective insomnia phenotype, we combined DSM-IV criterion with total sleep time from PSG with a cutoff of 360 min, allowing the classification of 6 groups: good sleeper TST≥360min, good sleeper TST<360min, insomnia symptoms TST≥360min, insomnia symptoms TST<360min, DSM-IV insomnia TST≥360min and DSM-IV insomnia TST>360min. Self-reported sleep duration was used to classify the individuals as short (<6 hours), average (6 to 8 hours) and long (>8 hours) sleepers. The LTL was measured using quantitative real-time polymerase chain reaction. Based on its distribution, we considered LTL<10 th percentile as short telomere and LTL≥10 th percentile as no-short telomere. Results: After adjustment for sex, age and body mass index, only DSM-IV insomnia (OR=2.654, 95%CI=1.025–6.873, p=0.044), DSM-IV insomnia TST<360min (OR=4.205, 95%CI=1.097–16.117, p=0.036) and long-sleepers (OR=2.177, 95%CI=1.189–3.987, p=0.012) were independently associated with short telomere. The final logistic regression model showed that age (OR=6.873, 95%CI=3.757–12.572, p<0.0001) and long-sleepers (OR=2.276, 95%CI=1.243–4.166, p=0.008) were the factors associated with short telomere. Conclusion: Taken together, our findings support the existence of an association between objective and subjective sleep parameters and the molecular pathways of aging, especially those related to telomere length maintenance. Support (If Any): This work was supported by grants from AFIP, FAPESP and CNPq.